Questionnaire identifying management practices surrounding calving on spring-calving dairy farms and their associations with herd size and herd expansion. (9th February 2016) - Cummins, C.; Berry, D. P.; Sayers, R.; Lorenz, I.; Kennedy, E.
Abstract : Healthy calves are fundamental to any profitable dairy enterprise. Research to-date, has focused on year-round calving systems which experience many different challenges compared to spring-calving systems. The objective of the present study was to determine the on-farm dry cow, calving, and colostrum management practices of spring-calving dairy production systems, and quantify their associations with herd size and herd expansion status (i.e. expanding or not expanding). Information on these management practices was available from a survey of 262 Irish spring-calving dairy farmers, representative of the Irish national population. Herd expansion in the 2 years before, and the year that the survey was conducted was not associated with any of the management practices investigated. Fifty-three percent of respondents had an average calving season length of 10 to14 weeks with 35% of herds having a longer calving season. Previous research in cattle has documented that both colostrum source and feeding management are associated with the transmission of infectious disease from cow to calf. In the present study 60% of respondents fed calves colostrum from their own dam; however, 66% of those respondents allowed the calf to suckle the dam, 23% of survey respondents fed calves pooled colostrum. Larger herds were more likely ( P <0.01) to use pooled colostrum supplies, while smaller herds were more likely ( P <0.05) to allow the calf to suckle the dam. The majority (86%) of respondents had stored supplies of colostrum; average-sized herds had the greatest likelihood of storing colostrum ( P <0.05), compared to other herd sizes; larger sized herds had a lesser likelihood ( P <0.05) of storing colostrum in a freezer, compared to other herd sizes. Although freezing colostrum was the most common method used to store colostrum (54% of respondents), 17% of respondents stored colostrum at room temperature, 29% of which stored it at room temperature for greater than 4 days. The results from the present study indicate that a particular focus needs to be placed on calving and colostrum management because this study has highlighted a number of areas which are below international standards, and may have repercussions for calf health. Furthermore, management practices on larger farms could be improved and, as these represent the future of dairy farming, a focus needs to be placed on them. Expanding herds are not a particular concern as herd expansion, independent of herd size, does not seem to be associated with calving and colostrum management practices on Irish spring-calving dairy herds.